A novel power system operation simulation method considering multi-state models of coal-fired power unit: a case study of coal-fired power transformation in a certain region of China. Issue 1 (February 2021) - Yue, Hao; Zheng, Yanan; Han, Xue; Li, Shunxin; Guo, Zheyu; Wang, Huiji; Yang, Jingang
Abstract: Coal-fired power has played an important role in the power systems, but its operational characteristics, especially the flexibility characteristics is modelled relatively simple in the current operation simulations. Given the background of a rapid development of renewable energy and a sustainable transformation of power systems in China, it is essential to build a refined model of coal-fired power units that can be incorporated into an operation simulation method. First, this study provides an analysis on the flexibility characteristics of coal-fired power units, including the minimum stable output, ramp limit and minimum up/down time. Subsequently, a multi-state probabilistic model of coal-fired power units is proposed. This study also constructs a sequential operation simulation method based on the universal generation function (UGF) method that incorporates multiple states of coal-fired power units. Finally, this study provides a development and transformation pathway for coal-fired power plants in the North Hebei (NH) region and suggestions for promoting a sustainable development of the power system based on the proposed method and multi-state model.